2020
DOI: 10.1155/2020/3921074
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha Deficiency Improves Endothelial Function and Cardiovascular Injury in Deoxycorticosterone Acetate/Salt-Hypertensive Mice

Abstract: It has been shown that the inflammatory cytokine tumor necrosis factor α (TNFα) plays a role in the development of hypertension and end-stage renal diseases. We hypothesize that TNFα contributes to endothelial dysfunction and cardiac and vascular injury in deoxycorticosterone acetate (DOCA)/salt-hypertensive mice. The wild-type or TNFα-deficient mice were uninephrectomized and implanted with DOCA pellet treatment for 5 weeks; the mice were given either tap water or 1% NaCl drinking water. DOCA mice developed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
9
0
5
Order By: Relevance
“…(43) In addition, studies in animal models and humans showed a protective effect of anti-TNF-α therapies on blood vessels in inflammatory and cardiovascular diseases. (44)(45)(46) Furthermore, Zhang et al (47) reported that blocking of TNF-α receptor controlled aortic atherosclerosis by reducing VCAM-1 expression in vivo. This is in agreement with the present findings that showed the significant elevation of TNF-α in the untreated rheumatoid group when compared to control group, the significant negative correlation between TNF-α and vascular reactivity and the significant positive correlation between TNF-α with VCAM-1 level.…”
Section: Discussionmentioning
confidence: 99%
“…(43) In addition, studies in animal models and humans showed a protective effect of anti-TNF-α therapies on blood vessels in inflammatory and cardiovascular diseases. (44)(45)(46) Furthermore, Zhang et al (47) reported that blocking of TNF-α receptor controlled aortic atherosclerosis by reducing VCAM-1 expression in vivo. This is in agreement with the present findings that showed the significant elevation of TNF-α in the untreated rheumatoid group when compared to control group, the significant negative correlation between TNF-α and vascular reactivity and the significant positive correlation between TNF-α with VCAM-1 level.…”
Section: Discussionmentioning
confidence: 99%
“…TNF α is one of the best described inflammatory cytokines in disturbed insulin signaling [ 36 , 37 ]; the infiltrating macrophages are a major source of TNF α in the vascular wall [ 18 ]. Recently, we [ 38 ] have shown that genetic knockout of TNF α gene lowers blood pressure and vascular inflammation and protects against endothelial dysfunction and vascular injury in DOCA salt-sensitive hypertension. Here, we showed that TNF α expression was significantly increased in the vasculature of hypertensive DS rats; macrophage depletion reduced vascular TNF α expression and inhibited NF κ B and JNK activation associated with the improvement of vascular insulin signaling and insulin-mediated vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelium-dependent vasorelaxation to acetylcholine or endothelium-independent relaxation to sodium nitroprusside was determined using an organ bath chamber (DMT Inc., Denmark) as previously described (Cai et al, 2020). The thoracic aorta was cut into 3-mm aortic rings, and the aortic rings were contracted twice with KPSS solution containing 60 mmol/L KCL.…”
Section: Organ Chamber Experimentsmentioning
confidence: 99%
“…The classically activated M1 macrophages are usually produced during cell-mediated host immune response and typically induced by lipopolysaccharide (LPS) or Th1 cytokines, such as tumor necrosis factor (TNF)α and interferon (IFN)γ (Zhang et al, 2012;Dungan et al, 2014;Orecchioni et al, 2019). M1 macrophages are more susceptible to the migration of the vascular wall and the release of inflammatory cytokines, such as TNFα and interleukin (IL)-1β, which may initiate vascular inflammation, oxidative stress, and vascular damage (Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%